Clinical and VNG Features in Anterior Canal BPPV—An Analysis of 13 Cases - Porwal, Prateek; V. R., Ananthu; Pawar, Vishal; Dorasala, Srinivas; Bijlani, Avinash; Nair, Prem; Nayar, Ravi (Frontiers in Neurology, 2021)
Objective. To define diagnostic VNG features in Anterior Canal BPPV during positional testing (Dix Hallpike, Supine head hanging and McClure Pagnini tests). Study Design. A retrospective study of patients diagnosed with Anterior Canal BPPV across four referral centres in New Delhi, Kochi, Bangalore and Dubai. Subjects and Methods. Clinical records of 13 patients of AC BPPV out of 1350 cases, during a three year period, were reviewed and analysed jointly by four specialists. Results –Four patients had positional down beating nystagmus with symptoms of vertigo on bilateral DHP maneuver. Seven cases had positional down beating nystagmus only on one side of DHP. Typical down beating nystagmus was seen in 10 out of 13 cases on straight head hanging maneuver. Down beating torsional nystagmus was seen in 6 out of 13 cases. Downbeating with horizontal nystagmus was seen in three cases (in DHP and MCP mainly) while pure down beating nystagmus on SHH was seen in four cases only. Conclusion. We conclude that the Anterior Canal BPPV is a rare but definite entity. It may not be apparent on positional testing on the first time, so repeated testing may be needed. The most consistent diagnostic maneuver is SHH though there were patients in whom findings could be elicited only on DHP testing. We recommend a testing protocol that includes DHP testing on both sides and SHH. MCP testing may also evoke DBN with or without torsional component. Reversal of nystagmus on reversal of testing position is unusual but can occur. Yacovino maneuver is effective in resolving AC BPPV. We also propose a hypothesis that explains why DHP testing is sensitive to AC BPPV on either side, whereas MCP lateral position on one side is sensitive to only one side AC BPPV.